Digital entrepreneurship from cellular data: How omics afford the emergence of a new wave of digital ventures in health - Hannes Rothe; Katharina Barbara Lauer; Callum Talbot-Cooper; Daniel Juan Sivizaca Conde (Electronic Markets, 2023)
Data has become an indispensable input, throughput, and output for the healthcare industry. In recent years, omics technologies such as genomics and proteomics have generated vast amounts of new data at the cellular level including molecular, structural, and functional levels. Cellular data holds the potential to innovate therapeutics, vaccines, diagnostics, consumer products, or even ancestry services. However, data at the cellular level is generated with rapidly evolving omics technologies. These technologies use scientific knowledge from resource-rich environments. This raises the question of how new ventures can use cellular-level data from omics technologies to create new products and scale their business. We report on a series of interviews and a focus group discussion with entrepreneurs, investors, and data providers. By conceptualizing omics technologies as external enablers, we show how characteristics of cellular-level data negatively affect the combination mechanisms that drive venture creation and growth. We illustrate how data characteristics set boundary conditions for innovation and entrepreneurship and highlight how ventures seek to mitigate their impact.
Keywords: M15; 620; Digital entrepreneurship; Digital innovation; Omics; Health data; External enabler